Consistency data of peak expiration flow, SpO2 level and heart rate measurement using spirometer volume (SpiroLuME) device - Muhammad Amir Aikal, Azmin; Mohd Azrul Hisham, Mohd Adib (TWIST Journal, 2023)
Currently, most respiratory system equipment has constraints preventing rapid and straightforward readings. Additionally, respiratory disorders require continual attention. To address this issue, the Spirometer volume so-called SpiroLuME device has been successfully developed to observe lung capacity performance. This research attempts to evaluate the reliability of the device's data using accurate patient information. Arduino Nano serves as the microprocessor, pressure sensor, oximeter sensor, and LCD screen display for the SpiroLuME device. The device can monitor and measure the user's peak expiratory flow (PEF), SpO2, and heart rate. Based on the preliminary test, the typical values range from 3.5 to 7 L/s, or 50 to 80 percent of the patients' maximum flow rate, at a heart rate between 60 and 96 beats per minute. Moreover, the oxygen level data range is 94% to 98%. The efficiency of the device has been compared with the existing device. As a result, the SpiroLuME device provides accurate and consistent PEF, SpO2, and heart rate readings for all patients.